Strategy safari the complete guide through the wilds of strategic management - Mintzberg, Henry (Harlow, FT Prentice Hall, 2009)
Strategy is the most prestigious but also the most confusing part of business. Managers are constantly bombarded with new jargon and the latest fads promising the magic bullet for every strategic problem. The world of strategy can seem to be an impenetrable jungle. Strategy Safari presents a powerful antidote to the dilemma of needing to know about strategy and yet not being able to find any comprehensible guidelines. This revised edition is a comprehensive, colourful and illuminating tour through the wilds of strategic management.
Includes bibliographical references (p. [397]-431) and index.
Keywords: Strategic planning